The Importance of Demonstration Method for Improving Students' Understanding of Geometric Concepts in Mathematics: A Qualitative Study - Obe, Melquiano; Magno Ximenes, Salvador (Jurnal PEKA (Pendidikan Matematika), 2026)
ABSTRACT: The demonstration method is essential for implementing mathematics learning for students in basic education in Timor-Leste. This research aims to examine teachers' ways of giving importance to and implementing demonstration methods in the discipline of mathematics. A qualitative method with a descriptive design was applied to explore the ideas and experiences of participants in the field. A mathematics teacher and five students were important participants in this research. These participants were selected using purposive sampling techniques, which involved them based on their experience, confidence, and ability to provide accurate data. Data were collected through interviews, observation, and documentation methods. Interview data were analysed using thematic techniques, and observation and documentation data were applied with content analysis techniques. The data were validated with triangulation techniques. The research results revealed that teachers attached importance to the use of demonstration methods, which had a positive effect on students' mathematics learning performance. The results of observation and documentation also confirm that teachers have a desire to use the method because it offers substantial benefits for students' learning. Demonstration methods become a positive element in teachers' teaching and students' learning of mathematics to improve the results of students' holistic education in Timor-Leste.   ABSTRAK: Metode demonstrasi sangat penting untuk mengimplementasikan pembelajaran matematika bagi siswa pendidikan dasar di Timor-Leste. Penelitian ini bertujuan untuk mengkaji cara guru memberikan perhatian dan mengimplementasikan metode demonstrasi dalam disiplin matematika. Metode kualitatif dengan desain deskriptif diterapkan untuk mengeksplorasi gagasan dan pengalaman partisipan di lapangan. Seorang guru matematika dan lima siswa merupakan partisipan penting dalam penelitian ini. Partisipan ini dipilih menggunakan teknik purposive sampling, yang melibatkan mereka berdasarkan pengalaman, kepercayaan diri, dan kemampuan mereka untuk memberikan data yang akurat. Data dikumpulkan melalui metode wawancara, observasi, dan dokumentasi. Data wawancara dianalisis menggunakan teknik tematik, dan data observasi dan dokumentasi diterapkan dengan teknik analisis isi. Data divalidasi dengan teknik triangulasi. Hasil penelitian menunjukkan bahwa guru memberikan perhatian pada penggunaan metode demonstrasi, yang memiliki pengaruh positif terhadap prestasi belajar matematika siswa. Hasil observasi dan dokumentasi juga menegaskan bahwa guru memiliki keinginan untuk menggunakan metode tersebut karena menawarkan manfaat yang substansial bagi pembelajaran siswa. Metode demonstrasi menjadi elemen positif dalam pengajaran guru dan pembelajaran matematika siswa untuk meningkatkan hasil pendidikan holistik siswa di Timor-Leste.